Character Building Through Counseling: The Reducement of Truancy with Cognitive Restructuring Technique: Array - Imroatul Hayyu Erfantinni; Roiyan One Febriani; Dian Eka Aprilia Fitria Ningrum; Vannisa Aviana Melinda (Islamic Guidance and Counseling Journal, 2019)
The purpose of this study is to determine the effectiveness of cognitive restructuring technique to reduce students’ truant behavior of Surabaya Pharmacy School. This study used experimental methods with Randomized Pretest-Posttest Control Group Design. The stage of the study was the preparation, the implementation, and the final stage. The subject of study was twelve students of Surabaya Pharmacy School from first, second, and third grades taken at random through the student truancy scale and divided into two groups, control and experiment group. The intervention is done by doing the counseling group with cognitive restructuring technique to reduce the student’s truancy behavior. The Data was analyzed using SPSS Paired Sampled T-Test. The analysis result showed that there was a significant difference before and after the intervention using cognitive restructuring in the experiment group. Therefore, the technique of cognitive restructuring is effective to reduce student's truancy at Surabaya Pharmacy School.